Navigating Consumer Behaviour: Exploring the Influence of Fashion Trends and Social Media on Gen Z and Millennial Consumption in West Java - Dewi, Yasdiafiani; Indra, Indra (Journal of Applied Management Research, 2024)
Understanding consumer behaviour is crucial for assessing the economic well-being of individuals or households. However, with the advancement and modernization of society, individuals tend to impose their desires on consumption, leading to a consumeristic. This study investigates the impact of fashion trends and social media on consumption behavior among Generation Z and Millennials in West Java Province using partial least squares structural equation modeling (PLS-SEM). Primary data collected through surveys were analyzed. The results reveal that fashion trends significantly influence consumption behavior, while social media has a minimal impact. This suggests that efforts to reduce consumerism's impact should focus on addressing the influence of fashion trends. However, leveraging social media for educational campaigns promoting responsible consumption remains crucial.